Skin-to-Skin Contact: A Comforting Place With Comfort Food. Issue 6 (November 2015) - Ludington-Hoe, Susan M.
Abstract : ABSTRACT: Birth and the newborn environment are stressful, especially for preterm infants who have to contend with medical conditions while adapting to the extrauterine world. Therefore, preterm newborns are excellent candidates for comforting measures. Skin-to-skin contact is the best way to provide comfort in several of the realms of Kolcaba's Comfort Theory. Evidence suggests that skin-to-skin contact between the mother and newborn changes the discomforting newborn environment into one that is profoundly comforting. Skin-to-skin contact promotes infant physiologic stability and warmth, helps in organizing infant sleep, reduces stress and pain, and makes breast milk readily available. Comfort to the newborn can be effectively accomplished by skin-to-skin contact. Abstract : Evidence suggests skin-to-skin contact between the mother and newborn provides a comforting environment. Skin-to-skin contact promotes infant physiologic stability and warmth, helps in organizing infant sleep, reduces stress and pain, and makes breast milk readily available. Comfort to the newborn can be effectively accomplished by skin-to-skin contact.